Estimating nutrient concentrations and uptake in rice grain in sub-Saharan Africa using linear mixed-effects regression - Rakotoson, T.; Senthilkumar, Kalimuthu; Johnson, J.M.; Ibrahim, A.; Kihara, Job Maguta; Sila, Andrew M.; Saito, Kazuki (Elsevier, 2023)
Context or problem Quantification of nutrient concentrations in rice grain is essential for evaluating nutrient uptake, use efficiency, and balance to develop fertilizer recommendation guidelines. Accurate estimation of nutrient concentrations without relying on plant laboratory analysis is needed in sub-Saharan Africa (SSA), where farmers do not generally have access to laboratories.